2017
DOI: 10.1016/j.cllc.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response and Prophylactic Cranial Irradiation Are Prognostic Factors in a Real-life Limited-disease Small-cell Lung Cancer Patient Cohort Comprehensively Staged With Cranial Magnetic Resonance Imaging

Abstract: In real-life patients comprehensively staged with cranial magnetic resonance imaging, treatment response and PCI strongly correlated with prolonged OS, TTP, and BMFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
3
16
1
Order By: Relevance
“…Other research reports that lung cancer is more prone to bone metastases because of the microenvironment of the bone that is affected by the bone matrix, the immune system cells, and the same cancer cells (Roato, 2014). At the time of the initial diagnosis, approximately 20% of patients with SCLC have detectable brain metastases (Eze et al, 2017), which is roughly in line with our findings. According to the most recent Eighth Edition of the Tumor, Node, and Metastasis (TNM) Classification of Lung Cancer, a larger tumor indicates a higher T stage (Rami-Porta et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Other research reports that lung cancer is more prone to bone metastases because of the microenvironment of the bone that is affected by the bone matrix, the immune system cells, and the same cancer cells (Roato, 2014). At the time of the initial diagnosis, approximately 20% of patients with SCLC have detectable brain metastases (Eze et al, 2017), which is roughly in line with our findings. According to the most recent Eighth Edition of the Tumor, Node, and Metastasis (TNM) Classification of Lung Cancer, a larger tumor indicates a higher T stage (Rami-Porta et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…However, our study showed different results. Eze et al [ 17 ] described a prognostic role of PCI in LS-SCLC and described a similarly significant magnitude of this benefit regardless of brain MRI after initial treatment, and this supported our results. There may be limits to imaging-guided evaluation for these conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Another retrospective study showed that PCI strongly correlated with prolonged OS and BMFS for patients without BM on contrast-enhanced MRI. 25 In our study, for patients showing no BM on MRI after definitive CRT, PCI conferred less BM incidence and better OS. However, a significant portion of patients may choose not to undergo PCI when presented with the potential neurologic toxicities.…”
Section: Discussionmentioning
confidence: 48%